CIRCULATION OF INDIAN OCEAN WATERS EAST OF MALDIVES DURING THE POST MONSOON PERIOD - Ramamirtham, C P (Indian Journal of Fisheries, 2011)
The circulation patterns in the Maldive region between the 71° and 80°E meridians within the equator and 8°N are discussed. It is observed that a large cyclonic gyre exists in the northern regions and an anticyclonic one in the southern region, mainly in the subsurface layers. These are supposed to be associated with divergence and convergence phenomena occurring in the area. The influence of the Maldive islands and the associated bottom topography in the formation of these circulation patterns is indicated.